Deep Learning Approach in Improving Critical Thinking Skills of Elementary School Students - Muhammad Aidil Sudarmono; Hasan; Halima (Jurnal Penelitian Pendidikan IPA, 2025)
A deep learning approach in education that creates deep, meaningful, and exhilarating learning experiences, as well as developing students' critical thinking skills. The implementation of this approach has great challenges, especially in terms of teacher competence, curriculum, and supporting facilities. The main objective of this learning is to equip students with critical thinking skills that will not only be useful in school, but also in their daily lives. The research method used is a literature study, which aims to review and analyze various relevant previous research. Data were obtained through searching, identification, and selection of literature indexed in Scholler, and Scopus. Relevant literature was selected based on topic relevance and publication quality, with data analysis using qualitative techniques based on content analysis, including categorization, synthesis of findings, and narrative analysis. The results of the study show that the epistemological gap in teacher competence is the main obstacle in implementing deep learning effectively. Teachers who lack reflective understanding and critical literacy can hinder the goal of deep learning. In addition, a curriculum that does not support active learning based on 21st century skills is also a challenge. Project-based, collaborative, and problem-based learning can improve students' critical thinking skills, but it requires adjustments in the education system. Based on these findings, strategic measures such as improved teacher training, flexible curriculum changes, and the provision of adequate support facilities are essential to optimize the application of deep learning in education. With the right application, deep learning can produce students who are more critical, creative, and ready to face global challenges.